PRINSIP EDUPRENEURSHIP MENURUT PERSPEKTIF ISLAM - Ridha Raudah Nur; Subiyantoro Subiyantoro (Universitas Labuhanbatu, 2022)
The purpose of this reseach is to know the principle of edupreneurship according to the Islamic perspertive. The reseach method that the author uses is qualitative-descriptive with a library research approach. The data collection technique here is documentation. that the principles of edupreneurship in the view of Islam are to optimize the various potentials possessed in order to produce scientific added value as well as relevant economic added value in the field of Islamic education. Islamic edupreneurship will develop students' habits in entrepreneurship to remain creative and innovative, such as writing books according to their respective interests and fields, or carrying out other activities that can provide added value economically. As a result, it will bring students to change who initially as users then turn into producers. The results of the research from the principle of edupreneurship according to this Islamic perspective are self-confidence, initiative in an energetic sense, focus on tasks and results, far-sighted, leadership spirit, dare to take risks, calculating, communicative, reflective, originality, innovative, creative, flexible. wise in making policies and decisions. Keywords: Edupreneurship, Islam